2008
DOI: 10.2106/jbjs.f.00531
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Macrophages in Early Healing of a Tendon Graft in a Bone Tunnel

Abstract: Macrophage depletion following anterior cruciate ligament reconstruction resulted in significantly improved morphologic and biomechanical properties at the healing tendon-bone interface, which we hypothesize are due to diminished macrophage-induced TGF-beta production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
137
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 155 publications
(145 citation statements)
references
References 45 publications
5
137
1
2
Order By: Relevance
“…effect of alendronate on tunnel and peri-tunnel bone and week 2-ultimate load and the effect was most marked at the tibial tunnel metaphysis. The effects of alendronate on the improvement of tendon graft to bone tunnel healing were consistent with the results of Thomopoulos et al (2007) and Hays et al (2008). Bisphosphonate was reported to suppress bone loss and improved tendonto-bone repair strength in a flexor tendon canine model (Thomopoulos et al, 2007).…”
Section: Fig 11supporting
confidence: 86%
See 2 more Smart Citations
“…effect of alendronate on tunnel and peri-tunnel bone and week 2-ultimate load and the effect was most marked at the tibial tunnel metaphysis. The effects of alendronate on the improvement of tendon graft to bone tunnel healing were consistent with the results of Thomopoulos et al (2007) and Hays et al (2008). Bisphosphonate was reported to suppress bone loss and improved tendonto-bone repair strength in a flexor tendon canine model (Thomopoulos et al, 2007).…”
Section: Fig 11supporting
confidence: 86%
“…Alendronate has been reported to suppress bone loss and improve tendonto-bone repair strength in a flexor tendon canine model (Thomopoulos et al, 2007). In another study, clodronate was reported to induce macrophage apoptosis and promote tendon graft to bone tunnel healing (Hays et al, 2008). The first study was not an ACL reconstruction model and the second study used the non-nitrogen-containing bisphosphonate, which has different mechanisms of action compared to nitrogen-containing bisphosphonate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inflammatory stage begins within the first week of rotator cuff repair and is characterized by the infiltration of neutrophils and recruited macrophages. These recruited macrophages secrete transforming growth factor b1 (TGFb1), which increases proteinase activity and collagen formation [26]. These early-recruited macrophages contribute to the formation of fibrovascular scar tissue; it is likely TGF-b1 secretion is the mechanism of scar tissue formation in the presence of recruited macrophages.…”
Section: Biology Of Bone-to-tendon Healingmentioning
confidence: 99%
“…These early-recruited macrophages contribute to the formation of fibrovascular scar tissue; it is likely TGF-b1 secretion is the mechanism of scar tissue formation in the presence of recruited macrophages. Local macrophages are also present in smaller numbers in the repairing bone-to-tendon insertion point; local macrophages are thought to have a positive anabolic function opposed to the catabolic function observed in the recruited macrophages [26]. Additionally, inflammation occurs after tendon overuse injuries and may serve as a protective mechanism in this setting [43].…”
Section: Biology Of Bone-to-tendon Healingmentioning
confidence: 99%